2009
DOI: 10.1111/j.1551-2916.2009.03118.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization and Luminescent Properties of a Red Phosphor Series: Y2−xEux(MoO4)3 (x=0.4–2.0)

Abstract: A series of rare earth molybdates, Y2−xEux(MoO4)3 for x=0.4, 0.8, 1.2, 1.6 and 2.0 were prepared by solid‐state method and their crystal structures, photo luminescent characteristics were investigated. The powders are mainly studied for their red light emission efficiency under near UV excitation. The crystal structures of the powders were found to depend on annealing temperature and the yttrium concentration. Mixtures of monoclinic (C2/c) and orthorhombic (Pba2, Pbna) structures were formed in varying proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…15 At present, many attentions have been attracted to rare earth ions activated alkaline earth molybdate compounds acting as phosphors for LEDs thanks to their efficient energy transfer from the broad charge transfer band in near UV region, as well as chemical and thermal stability. [16][17][18][19] It has been found that the coordination number groups make them suitable for near UV pumped LEDs. They were usually used as red phosphors owing to the high energy transfer efficiency in the MoO 6 -Eu 3+ systems.…”
Section: Introductionmentioning
confidence: 99%
“…15 At present, many attentions have been attracted to rare earth ions activated alkaline earth molybdate compounds acting as phosphors for LEDs thanks to their efficient energy transfer from the broad charge transfer band in near UV region, as well as chemical and thermal stability. [16][17][18][19] It has been found that the coordination number groups make them suitable for near UV pumped LEDs. They were usually used as red phosphors owing to the high energy transfer efficiency in the MoO 6 -Eu 3+ systems.…”
Section: Introductionmentioning
confidence: 99%
“…Trivalent Eu ion, as one of the promising species that provide optical emission in red color regions, has been doped in various compounds. Trivalent Eu ion has been expected as one of the promising species that provide optical devices in red color regions and many investigations have been conducted in various compounds [11][12][13]. Trivalent Eu emission is very useful for studying the nature of metal coordination in various systems owing to its non-degenerate emitting 5 D 0 state.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive research has been carried out on rare-earth-doped phosphors because of several important superior properties, such as luminescent characteristics,stability in vacuum, and corrosion-free gas emission under electron bombardment compared with traditional cathode ray tube used in current field emission displays [7,8]. Trivalent Eu ion, as one of the promising species that provide optical emission in red colour regions, has been doped in various compounds [9][10][11]. However, to the best of our knowledge, there is no report on the research of M 7 Sn(PO 4 ) 6 (M = Sr, Ba) phosphor activated by rare earth or transition metal.…”
Section: Introductionmentioning
confidence: 99%